Why do people self‐sacrifice for their country? The roles of identity fusion and empathic concern. Issue 1 (8th November 2021) - Landabur, Rodrigo; Miguez, Gonzalo; Laborda, Mario A.; Salinas, María I.
Abstract: Identity fusion with a group, a feeling of connection with it, is a good predictor of extreme pro‐group behavior, an action to favor or protect the group, including self‐sacrifice. Relational ties and personal distress (self‐oriented emotional reaction; e.g., anxiety, distress) toward ingroup members in need have been evaluated separately as mediators of the relationship between identity fusion and pro‐group self‐sacrifice. Another mediator could be empathic concern (other‐oriented emotional reaction; e.g., compassion, sympathy), but it has not been considered in the literature. We related those three mediators in a model. The objective was to analyze whether relational ties mediate the relationship between identity fusion and pro‐country self‐sacrifice whereas both empathic concern and personal distress mediate the association between relational ties and pro‐country self‐sacrifice. We expected that identity fusion with the country leads to more relational ties, which in turn evokes both empathic concern and personal distress, and those emotional reactions promote more and less pro‐country self‐sacrifice, respectively, with more effect of empathic concern than personal distress. We considered the country as the group reference because it is the most used in identity fusion research. In a sample of university students ( N = 539), the results supported this model: Identity fusion promoted relational ties, which in turn evoked empathic concern and personal distress. Then, the last two variables predicted more and less self‐sacrifice, respectively, with more effect of empathic concern than personal distress. We discussed the theoretical implications of the model, especially the relationship of identity fusion with empathic concern and personal distress—traditional explanations for pro‐group behavior—considering the different motivations associated to both emotional reactions. Despite the limitations associated with the measurements, the data supported the model that relates variables not previously explored jointly.